2018
DOI: 10.1007/s10803-018-3744-1
|View full text |Cite
|
Sign up to set email alerts
|

Distractor Inhibition in Autism Spectrum Disorder: Evidence of a Selective Impairment for Individuals with Co-occurring Motor Difficulties

Abstract: Although most researchers agree that individuals with Autism Spectrum Disorder (ASD) exhibit atypical attention, there is little consensus on the exact nature of their deficits. We explored whether attentional control in ASD varies as a function of motor proficiency. Nineteen children with ASD and 26 typically-developing controls completed the Movement Assessment Battery for Children and two ocular motor tasks requiring them to generate a saccade toward, and fixate, a visual target in the presence or absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Saccade latency was not related to measures of social functioning. Lindor et al (2019) explored the influence of distractors and motor proficiency on saccadic functioning. Autism symptomatology (SRS‐2 Total score) significantly predicted final saccade accuracy, but only in the context of low motor proficiency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Saccade latency was not related to measures of social functioning. Lindor et al (2019) explored the influence of distractors and motor proficiency on saccadic functioning. Autism symptomatology (SRS‐2 Total score) significantly predicted final saccade accuracy, but only in the context of low motor proficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Males were by far most represented across studies, ranging from 53% males (Lindor et al, 2019; White et al, 2015) to male only samples (Del Valle Rubido et al, 2018; Franchini et al, 2016; Fujioka et al, 2016; Jones & Klin, 2013; Klin et al, 2002; Sasson et al, 2007; Speer et al, 2007). Not only is this consistent with a greater incidence of ASD in males (Loomes et al, 2017), but also with the broader literature that has been biased toward predominantly male samples (Kirkovski et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This wide range of difficulties, which typically present in childhood, can impact the ability of people with ASD to acquire basic and important cognitive and motor skills required for typical lifelong development [Marko et al, 2015]. Besides the sensorial deficits, motor impairments have been commonly described in children and adolescents with ASD, such as lack of mimicry in abilities, interpersonal synchronization and motor coordination [Xavier et al, 2018], poor accuracy [Lindor, Rinehart, & Fielding, 2018], impairments in postural control [Miller, Cacola, Sherrod, Patterson, & Bugnariu, 2019], motor impairments in balance, gait, and coordination as well as autismspecific impairments in praxis/motor planning [Kaur, M Srinivasan, & N Bhat, 2018], and attentional engagement capacity [Bryson et al, 2018]. These findings raise questions regarding development of motor control and proprioception in young people with ASD [Xavier et al, 2018] and suggest that new approaches should be considered in order to enhance motor performance.…”
Section: Introductionmentioning
confidence: 99%
“…A further possible direction for future research could be to consider the roles of traits that overlap between neurodevelopmental disorders, and of co-occurrence of such conditions, in academic achievement. It is possible for neurodevelopmental disorders such as ASD, ADHD, and DCD to co-occur (Tal-Saban and Kirby, 2019;Miller et al, 2021), and there are often traits that are found in more than one of these conditions (Reiersen et al, 2008), for example, motor difficulties can be found in ASD and ADHD as well as DCD (Lindor et al, 2019;Miller et al, 2021). The current study examined whether traits of ASD, ADHD, and DCD could separately moderate the relationship between executive function and academic achievement, so future research could assess whether traits of these disorders together can moderate this relationship in students with clinical diagnoses, which could have notable implications for individuals who have been diagnosed with cooccurring ASD, ADHD, or DCD.…”
Section: Discussionmentioning
confidence: 99%
“…DCD is a neurodevelopmental condition involving difficulties with motor co-ordination (Zwicker et al, 2012;Omer and Leonard, 2021), and is thought to affect 5-6% of children (Zwicker et al, 2012;American Psychiatric Association, 2013). Individuals with autism and ADHD can perform poorly on tasks that assess motor skills even if they do not meet the diagnostic criteria for DCD (Lindor et al, 2019;Miller et al, 2021). These motor impairments can increase with age (Licari et al, 2020), and research by Tal-Saban et al (2014) found that three-quarters of young adults who had DCD also met diagnostic criteria for ADHD.…”
Section: Executive Function and Academic Achievement In Developmental...mentioning
confidence: 99%